2002
DOI: 10.1557/proc-757-ii5.4
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum in Nuclear Waste Glasses - Incorporation and Redox state

Abstract: The composition and structure of the mixed metal molybdates that can form in simulated high level nuclear waste (HLW) glass melts have been studied. It was found that molybdates of a tetragonal scheelite type were formed upon heat treatment of the simulated glass samples (representative of the slow cools experienced by the real vitrified product), and that these compounds are capable of incorporating the majority of the mono, di, and trivalent cations that would be present in a real HLW glass. In addition, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…This indicates that the presence of Fe in these glasses, which is present due either to waste loading or for waste compatibility reasons, has a significant and positive effect on the resistance of the wasteform to c-irradiation. It would be of interest, in future, to investigate this issue in connection with other redox active elements in radioactive waste glasses, such as Mo and Se [73][74][75][76][77]. Finally it may be concluded that c-radiation does not have a significant deleterious effect on the mechanical stability or composition of simulant inactive UK ILW and HLW glasses, up to the dose of 8 MGy.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the presence of Fe in these glasses, which is present due either to waste loading or for waste compatibility reasons, has a significant and positive effect on the resistance of the wasteform to c-irradiation. It would be of interest, in future, to investigate this issue in connection with other redox active elements in radioactive waste glasses, such as Mo and Se [73][74][75][76][77]. Finally it may be concluded that c-radiation does not have a significant deleterious effect on the mechanical stability or composition of simulant inactive UK ILW and HLW glasses, up to the dose of 8 MGy.…”
Section: Resultsmentioning
confidence: 99%
“…Molybdenum is a fission product coming from spent fuel reprocessing solutions, and is weakly soluble in glass [12][13][14][15]. When the content is higher than its solubility limit, processes of phase separation and of crystallization lead to the formation of heterogeneous glasses [16].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high field strength, Mo 6+ cation has a limited solubility in silicate and borosilicate glasses and crystallization of alkali or alkaline-earth molybdates may occur during melt cooling or heat treatment of glasses [3][4][5]. Indeed, according to EXAFS results giving the average Mo-O distance d(Mo-O) in silicate and borosilicate glasses [1,[6][7][8], the field strength F of Mo 6+ cation (F = 6/d(Mo-O) 2 ) ranges between 1.89 and 1.935 Å À2 (Table 1).…”
Section: Introductionmentioning
confidence: 99%